Medical Treatment of Pulmonary Arterial Hypertension - Sahay, Sandeep; Humbert, Marc; Sitbon, Olivier (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary arterial hypertension (PAH) is a progressive and life-threatening disease leading to right ventricular failure and death if left untreated. Over the past two decades, progress in the understanding of pathophysiological mechanisms of the disease has led to the development of medications targeting the three major pathways of endothelial dysfunction: prostanoids, endothelin-receptor antagonists, and phosphodiesterase type-5 inhibitors. Efficacy of PAH-targeted medications has been demonstrated in monotherapy through randomized clinical trials leading to their regulatory approval. However, despite the growing numbers of available PAH-targeted medications, many patients with PAH continue to deteriorate and the disease ultimately remains fatal. The availability of multiple classes of drugs targeting different pathophysiological pathways provides strong biological rationale for the use of combination therapy in PAH. Evidence to support this strategy is growing, and many studies have demonstrated that combination therapy, administered as either a sequential or an initial regimen, can improve long-term outcomes in PAH. Treatment strategy for PAH has thereby changed significantly over the past decade, combination therapy becoming progressively the gold standard of care in patients with PAH. This is underscored by the current European Society of Cardiology/European Respiratory Society guidelines, in which combination therapy now plays a central part in the treatment algorithm.
Keywords: hypertension, pulmonary; pulmonary arterial hypertension; therapy; prostacyclin; endothelin; nitric oxide; phosphodiesterase type-5